PEDAGOGICAL AND PSYCHOLOGICAL FOUNDATIONS FOR ENHANCING STUDENTS’ CREATIVE AND PROFESSIONAL ACTIVITY IN VISUAL ARTS LESSONS - Eshmatov Samariddin Hamza oʻgʻli (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
Abstract: This article examines the pedagogical and psychological foundations for enhancing students’ creative and professional activity in visual arts lessons. The study explores the use of interactive methods, project-based learning, motivation and encouragement systems, and consideration of students’ individual characteristics to develop their creative potential. The article also provides practical recommendations for organizing lessons effectively, creating a stimulating creative environment, and supporting students’ personal and professional development.